Interações medicamentosas entre idosos incluídos em um serviço de gerenciamento da terapia medicamentosa da atenção primária - Tayane Oliveira dos Santos (2018)
The Brazilian population is undergoing changes in the last decades with an increase in the proportion of elderly individuals. In general, aging is accompanied by increased comorbidities and use of multiple medications, which may lead to drug interactions (DI). DI are considered avoidable adverse events and may present severe and even fatal outcomes. In this context, the objective of the present study was to determine the prevalence of MI and among elderly people enrolled in a Medication Therapy Management (MTM) service in the municipality of Lagoa Santa, Minas Gerais (n = 436), associated factors and clinical consequences. Beers criteria (2015) was used to define DIs, which will be the depend variable in the study. The following were used as independent variables: sex, age, number of health problems, number of medications used, and Charlson's comorbidity index (CCI), diagnosis of hypertension, diabetes, heart failure, depressive disorder, arrhythmia, central nervous system (CNS) disease. The analysis of the associated factors was performed through univariate (Pearson's chi-square) and multivariate analysis (logistic regression). The significance level of 5% was adopted for all analyzes. 94.5% of the elderly used medications or more (n=408), condition for the occurrence of DI and had a mean of 70.2±7.8 years, 52.2% in the age range of 60 to 69 years and 61.3% were female. The prevalence of DI of the Beers criteria was 4.9%. After multivariate analysis, CNS disease, arrhythmia, number of medications and female gender were positively associated with IM presence. The prevalence of DI proposed by Dumbreck was 27.2%. After multivariate analysis, number of medications, heart failure and CCI greater than 1 were positively associated with IM presence. Therefore, it is worth emphasizing the importance of a holistic and totally individualized approach in the medication therapy management of the elderly patients, considering the DI and to minimize consequent adverse events.